NR4A receptors up-regulate the antiproteinase alpha-2 macroglobulin (A2M) and modulate MMP-2 and MMP-9 in vascular smooth muscle cells - Rodríguez-Calvo, Ricardo; Ferrán, Beatriz; Alonso, Judith; Martí-Pàmies, Ingrid; Aguiló, Silvia; Calvayrac, Olivier; Rodríguez, Cristina; Martínez-González, José (Thrombosis and Haemostasis, 2015)
Matrix metalloproteinases (MMPs) are associated with tissue remodelling and repair. In non-vascular tissues, NR4A receptors have been involved in the regulation of MMPs by transcriptional repression mechanisms. Here, we analyse alternative mechanisms involving NR4A receptors in the modulation of MMP activity in vascular smooth muscle cells (VSMC). Lentiviral overexpression of NR4A receptors (NOR-1, Nurr1 and Nur77) in human VSMC strongly decreased MMP-2 and MMP-9 activities (analysed by zymography and DQ-gelatin assays) and protein levels. NR4A receptors also down-regulated MMP-2 mRNA levels. Real-time PCR analysis evidenced that alpha-2-macroglobulin (A2M), but not other MMP inhibitors (TIMP-1 and TIMP-2) were up-regulated in NR4A-transduced cells. Interestingly, A2M was expressed in human vascular tissues including the smooth muscle media layer. While NR4A receptors increased A2M expression and secretion in VSMC, NR4A knockdown significantly reduced basal A2M expression in these cells. The direct transcriptional regulation of the human A2M promoter by NR4A receptors was characterised in luciferase reporter assays, electrophoretic mobility shift assays and by chromatin immunoprecipitation, identifying a NGFI-B response element (NBRE-71/-64) essential for the NR4A-mediated induction. The blockade of A2M partially prevented the reduction of MMPs activity observed in NR4A-transduced cells. Although mouse A2M promoter was unresponsive to NR4A receptors, vascular MMP expression was attenuated in transgenic mice over-expressing human NOR-1 in VSMC challenged with lipopolysaccharide. Our results show that the panproteinase inhibitor A2M is expressed in the vasculature and that NR4A receptors modulate VSMC MMP activity by several mechanisms including the up-regulation of A2M.
Keywords: Matrix metalloproteinases; vascular remodelling; gene expression; transcription factors; smooth muscle cells